Symptomatic epidural gas cyst treated with epidural block and percutaneous needle aspiration -A case report - Kang, Sang-Soo; Kim, Myoung-Sun; Ko, Kwang-Min; Park, Jung-Chan; Hong, Sung-Jun; Yoon, Young-Jun; Shin, Keun-Man (Korean journal of anesthesiology, 2012)
A 68-year-old woman suffered from lower back and radiating pain on her right buttock and posterior calf. Axial magnetic resonance imaging showed a 7 × 7 mm nodular lesion (T1 and, T2 low signal intensity) at the epidural space between the L5-S1 level and computed tomography revealed it was an epidural gas cyst. The authors performed an epidural block and percutaneous needle aspiration of the epidural gas cyst. The patient showed almost complete resolution of symptoms one year later. The authors suggest that an epidural nerve block with needle aspiration of a gas cyst could be an alternative treatment option for patients with a symptomatic epidural gas cyst before surgery.